Translation Errors from English into Indonesian Language of the Rich Young Man Story - Sanger. A; Lumoindong. B (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
This research aimed at identifying errors in translating phrases from English into Indonesian of The Rich Young Man Story in Gospel Matthew 19:16-26 (KJ Version) to Indonesia Masa Kini Bible Version, and what factors caused these errors. The study utilized a descriptive method with a qualitative approach as described by Cresswell and Lodico. The results of the research showed that there were several translation phrases errors found in the Indonesia Masa Kini Bible Version that were caused by translators' tendency to use free translation system, resulting in addition, omission, or replacement of phrases, as well as inaccuracies in selecting appropriate equivalents, making the translation sound unnatural in the target language. These errors indicated there are some incompetence on the translator’s part, namely lack of understanding of translation theory, errors in applying omission and addition strategies, the inability to understand English phrases, inability to interpret the meaning and message of the source text, and lack of concentration and carefulness while translating.